Fosfito no crescimento, nutrição fosfatada e aspectos da indução de resistência em milho - Ávila, Fabrício William de (2009)
The present work was intended to evaluate the effect of supplying of phosphite on the growth, phosphate nutrition and aspects of the induction of resistance in maize. An experiment in a completely randomized design was conducted in nutrient solution under greenhouse conditions, where two concentrations of P (1.6 mg L-1 = low phosphorus and 20 mg L-1 = adequate phosphorus) were combined with two forms of P supply [one completely in the form of phosphate (Pi) and another with 1/4th of Pi replaced by phosphite (Phi)]. The experiment was conducted with 20 replicates, amounting to 80 experimental plots, being each plot consisting of one plant in each pot. Out of those replicates, eight from each treatment were intended to the investigation of the kinetic parameters of uptake of 31P in the form of Pi. So, a trial was conducted in a completely randomized design, where two treatments were employed in the kinetic solution (25 mg L-1 of P supplied wholly in the form of Pi and 50 mg L-1 of P, being 25 mg L-1 given as Pi and 25 mg L-1 supplied as Phi) combined with the four treatments which were submitted to the plants throughout the cultivation. As regards the other plants, in six replicates of each treatment the following variables were studied: SPAD reading, leaf area, acidic phosphatase activity (AFA), weight of the dry matter of shoot (MSPA), root (MSR) and total (MST), P accumulation in the MSPA, MSR and MST, MSR:MSPA ratio, rates of efficiency of utilization (EUP), uptake (EAP) and translocation (ETP) of P and the contents of total P, inorganic P and organic P soluble in acid. In the other six remaining replicates, the activity of peroxidases (POXs) was evaluated and the quantification of the contents of total phenols and lignin accomplished. For the plants grown in low concentration of P, the replacement of 1/4th of Pi by Phi promoted a marked increased in the symptoms of P deficiency. That fact was stressed both visually and by the reduction of the leaf area, decreased weight of MSR, MSPA e MST, decrease of P accumulation in those tissues, low EUP and increase of AFA. However, in the plants grown at adequate concentration of P, Phi little influenced the growth and phosphate nutrition of these, where only reduction in the leaf contents of inorganic P soluble in acid and decreased accumulation of P in MSPA was found. In relation to the kinetic parameters, the values of Km for Pi, independent of the growing treatments were increased by the presence of Phi in the kinetic solution, showing that Phi inhibit competitively uptake of Pi in maize. But, Vmax was influenced only by the concentrations of P submitted in the cultivation of the plants, greatly increasing in the treatments with low P supply. It was also found that the replacement of 1/4th of Pi by Phi in phosphate fertilization promoted the rise of the lignin contents in the leaf tissues of the plant. The same effect was stressed for activity of POXs in the case of plants adequately supplied in P. That behavior makes clear the elicitor effect of phosphite on the defense mechanisms in maize.